(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Translation forms a scientific, artistic and procedural house that receives texts whose language and culture are peculiar. It probes them and explores their unique ideas and treasures to quench its thirst for it is a science and an end by itself. It has its bases, its factors, importance and tools, and it tries to quench others when it becomes a bridge between different nations and cultures and their various ways of thinking. From this perspective, the title is a kind of analysis, of what the subtitle is: the essence of translation, and the comparative literary research so that both will be the object of our study in continuation of previous studies whose echo could be seen by the reader directly or indirectly of for being similar